Epidemiology and Regional Predictors of COVID-19 Clusters: A Bayesian Spatial Analysis Through a Nationwide Contact Tracing Data - Hong, Kwan; Yum, Sujin; Kim, Jeehyun; Yoo, Daesung; Chun, Byung Chul (Frontiers in Medicine, 2021)
Purpose: Revealing the clustering risks of COVID-19 and prediction is essential for effective quarantine policies since clusters can lead to rapid transmission and high mortality in a short period. This study aimed to present which regional and social characteristics make COVID-19 the cluster with high risk. Methods: By analyzing the data of all confirmed cases (14,423) in Korea between January 10 and August 3, 2020, provided by the Korea Disease Control and Prevention Agency, we manually linked each case and discovered clusters. After classifying the cases into clusters as nine types, we compared the duration and size of clusters by types to reveal high-risk cluster types. Also, we estimated odds for the risk factors for COVID-19 clustering by a spatial autoregressive model using the Bayesian approach. Results: Regarding the classified clusters (n=539), the mean size was 19.21, and the mean duration was 9.24 days. The number of clusters was high in medical facilities, workplaces, and nursing homes. However, multilevel marketing, religious facilities, and restaurants/business-related clusters tended to be larger and longer when an outbreak occurred. According to the spatial analysis in COVID-19 clusters more than 20 cases, the global Moran's I statistics value was 0.14 (p<0.01). After adjusting the population size, the risks of COVID-19 clusters were related to male gender (OR=1.29) and low influenza vaccination rate (OR=0.87). After the spatial modeling, the predicted probability of forming clusters was visualized and compared with the actual incidence and local Moran’s I statistics at the posterior two months of the study period. Conclusions: COVID-19 makes different sizes of clusters in various contact settings; thus, precise epidemic control measures are needed. Also, detecting and screening for COVID-19 clusters may consider regional risks such as vaccination rate for predicting risk to control pandemic cost-effectively.